International Journal of Emergency Medicine - Ganti, Latha
The International Journal of Emergency Medicine is a high-quality Open Access journal which aims to bring to light the various clinical advancements and research developments attained over the world, thus helping the specialty forge ahead. It is directed towards physicians and medical personnel undergoing training or working within the field of Emergency Medicine. Disciplines covered include interesting clinical cases, the latest evidence-based practice and research developments in Emergency Medicine, including emergency pediatrics. The International Journal of Emergency Medicine focuses on the practice of Emergency Medicine in a variety of settings, from urban emergency departments and rural clinics in the developing world, to humanitarian and disaster situations. It aims to shed light on international advances in practice, education and research, with a single common goal: to reduce suffering and promote excellence in patient care worldwide.